PENERAPAN SISTEM SIMPAN TEMU KEMBALI INFORMASI BERBASIS SLIMS 9 BULIAN DI PERPUSTAKAAN POLITEKNIK NEGERI SRIWIJAYA PALEMBANG - Islamy Pratama, Rafqy Ariefa (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2025)
Sriwijaya Polytechnic Library Palembang has implemented SLiMS 9 Bulian-based Information Retrieval System (SSTKI). The purpose of the study was to evaluate the implementation, analyze its impact on library performance, and assess the level of user satisfaction. The research methodology involved data collection through observation, interviews with the head of the library, as well as searches of related literature. The results showed that the implementation of SLiMS 9 Bulian has made a positive contribution to the library's information management process. The system makes it easier to search, store and manage information, improve collection accessibility and optimize library resources. The positives are seen in the improved performance of library staff in providing more efficient services to users. This research also identifies some of the challenges in the implementation of the system and provides an in-depth understanding of the benefits and barriers of implementing Bulian 9 SLiMS-based library information system in an academic environment. It is expected to serve as a basis for other libraries planning to adopt a similar system, as well as contributing to further development in library information management in the digital era